Two new species of Hydroptilidae (Insecta: Trichoptera) from the Serra dos Carajás, Pará state, northern Brazil - de Liege Gama Neto, Jaime; Ribeiro, José Moacir Ferreira; Passos, Mahedy Araujo Bastos (Zootaxa, 2019)
Two new species of Hydroptilidae from Pará, Brazil, are described and illustrated: Costatrichia inaequalis sp. nov. is a distinctive species characterized principally by the lateral processes on tergum IX rounded and each bearing a long dorsal seta. Oxyethira carajas sp. nov. is characterized by the inferior appendages fused, incised mesally, narrowing posterolaterally, and each bearing a stout apical seta and having its ventral process blade-like. New distributional records are given for a species of Neotrichia for which the name is unpublished.